Correction of experimentally produced vesicoureteric reflux in the piglet by intravesical injection of Teflon. Issue 6436 (7th July 1984) - Puri, P; O'Donnell, B
Abstract : Vesicoureteric reflux was produced in eight piglets by opening their bladders and slitting the anterior intravesical wall of the ureter. Cystography confirmed the presence of bilateral reflux in six piglets and unilateral reflux in two. Six to eight weeks later the bladder was again opened and Teflon paste injected in the space behind the intravesical ureter, thereby creating a support for the submucosal ureter. Cystography four to six weeks after injection of Teflon paste showed absence of reflux in all animals. Intravenous pyelography showed obstruction at the vesicoureteric junction in only one of the 14 treated ureters and this was later confirmed at necropsy. Animals were followed up from one to six months and then were killed. Gross examination of the vesicoureteric region showed a well circumscribed subureteric Teflon mass of firm consistency, retaining its shape and position at the site of the injection. Histological examination showed encapsulation of the implant by a thin layer of fibrous tissue and a foreign body granulomatous reaction with histiocytes and giant cells within the implant. Hence it is technically feasible to correct experimentally produced vesicoureteric reflux in the piglet by intravesical injection of Teflon paste--a relatively inert material. It may now be possible to treat vesicoureteric reflux in man by endoscopic injection of Teflon behind the intravesical ureter.